I'm trying to integrate $e^{2x} \cdot \sin 3x dx$ using integration by parts technique. According to some websites my answer is incorrect.

My attempt was:

$\int e^{2x}\sin (3x) dx = [u=e^{2x}, du = 2e^{2x} , dv= \sin 3x, v= -1/3\cos 3x] = uv -\int vdu = -\frac{1}{3}e^{2x}\cos 3x + \frac {2}{3}\int e^{2x} \cos (3x) dx = [u=e^{2x}, du = 2e^{2x}, dv = \cos (3x), v = \frac{1}{3}\sin (3x)] = -\frac{1}{3}e^{2x} \cos3x + \frac{1}{3} e^{2x}\sin 3x -\frac{2}{3}\int e^2x \sin (3x) dx $

And so I get: $\frac {5}{3}\int e^{2x} \sin (3x)dx = -\frac{1}{3}e^{2x}\cos 3x + \frac{1}{3}e^{2x}\sin 3x$

And finally:

$\int e^{2x} \sin (3x)dx = \frac{1}{5}e^{2x} (\sin(3x)-\cos(3x))+C$.

According to the websites I checked the answer should be $\frac{1}{13}e^{2x}(2\sin(3x)-3\cos(3x) + C$.

Where is my mistake?


In your second integration by parts you forgot the factor of $\frac{2}{3}$ from the first one, so \begin{align*} ... &= -\frac{1}{3}e^{2x}\cos 3x + \frac{2}{3}\left(\frac{1}{3}e^{2x}\sin 3x - \frac{2}{3}\int e^{2x}\sin 3x\,dx\right) \\ &= -\frac{4}{9}\int e^{2x}\sin 3x\,dx - \frac{1}{3}e^{2x}\cos 3x + \frac{2}{9}e^{2x}\sin 3x. \end{align*} Now simplify.


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.